Pelaksanaan Pelayanan Publik Oleh Pemerintah Kelurahan Di Kota Jambi - Herma Yanti; M Kurniawan; Sayuti Abdullah (Jurnal LEX SPECIALIS, 2011)
Urban Village is one of the Regency / City is one of its functions to provide services to the community. This understanding is intended to see the implementation of community service by the government and the village of Tanjung Johor and Sungai Putri in the city of Jambi. Services provided include administrative services manufacture Identity Card, Certificate of Good Behavior, Land Letter, Certificate of Business and others. Services provided as is caused by a lack of public awareness to meet the administrative requirements necessary to menertbitkan certificate is required, the presence of foreign service officers, thus hampering the implementation of effective public services and efficient, so as to overcome done by providing legal counseling to community to increase public awareness and to delegate authority from the foreign service officials to be certain officials, so that the process of providing public services is not hampered Key Note : Implementation of the Public Service